Modular silacyclopropenes: synthesis and application for Si–H containing substrate functionalization. Issue 79 (15th September 2022) - Nobis, Matthias; Inoue, Shigeyoshi; Rieger, Bernhard
Abstract : We report an effective and versatile method to functionalize Si–H containing substrates with monofunctional silacyclopropenes as modular units in a hydrosilylation reaction. Abstract : A method to functionalize Si–H containing substrates with vinyl substituted silacyclopropenes has been developed. This provides an efficient and versatile technique to generate multi-functional silacyclopropene derivatives, ranging from small molecules to polymeric materials like polysiloxanes. Thus, access is given to a new class of functionalized materials that exhibits potential in a variety of possible applications.